The crime of witchcraft and sorcery according to Law 06/24 - Bouzerara Zeggar, Miryam (Journal of Human Sciences, 2025)
The crime of witchcraft and sorcery has recently spread widely, becoming a serious concern due to physical, psychological, and religious harm it causes. In response to the growth of this criminal phenomenon, The Algerian Criminal Legislator amended the legal classification of the crime from misdemeanour to aggravated offense and intensified the criminal penalty associated with it under the 06/24 amendment of penal Code. This was aimed at achieving both general and specific deterrence for anyone who dares to harm religious beliefs, the safety of individuals, and the stability and security of society.